Der Glanz der Schekhinah und Elisabets Verhüllung (Lukas 1,24) (lectio difficilior, 2005)
During the last thirty years, the Gospel of Luke has been a storm center concerning the question of women’s roles. One option was to see Luke as the celebrator of women`s dicipleship and strength. But this was profoundly problematizised by a second option that sees Luke as threatening any attempt made by women to find a voice in either society or church. My paper focuses on Luke 1,24-25, the hiding of Elisabet. We have to cope with a gesture of veiling which is not easily understood in modern Western societies and in Western exegesis. The Western perspective of Elisabet’s veiling has a threefold handicap: Seeing the woman means in our genderbiased culture to deal with a special question, a “woman’s concern”. So Elisabet is seen as a wife, an old woman, in sexualizing terms only, but she is not conceived in terms of Jewish piety and antique culture.Inspite of my gender sensitive reading, I suggest not to see the woman who hides herself (out of shame or other – psychological or dogmatic – reasons), but to embed Elisabet in the house of Aaron and the early Jewish Mysticism.